Serum HDL-C subfractions as predictors of cardiovascular calcification in hemodialysis patients: novel insights and clinical implications - Li, Dong-Yun; Sun, Wei; Zhou, Xiao-Tao; Wen, Yu; Zou, Yang (Frontiers in Medicine, 2024)
Objective: This study aims to explore the relationship between cardiovascular calcification (CVC) and serum levels of high-density lipoprotein cholesterol (HDL-C) and its subfractions in hemodialysis (HD) patients.Methods: HD patients and healthy participants were recruited based on specific inclusion and exclusion criteria. Various blood indicators were measured, and demographic information was recorded. HDL-C particle levels were quantified using lipophilic fluorescent dye staining and capillary electrophoresis (microfluidic platform).Coronary artery calcium scores and valve calcification were used to classify HD patients into calcification and non-calcification groups.Results: Compared to healthy participants, HD patients showed a significant increase in HDL-C, high-density lipoprotein 2 cholesterol (HDL2-C), and high-density lipoprotein 3 cholesterol (HDL3-C) levels (p <0.001). Further division of HD patients into calcification and non-calcification groups revealed higher serum HDL3-C concentrations (p =0.002) and a higher HDL3-C/HDL-C ratio (p =0.04) in the calcification group. Additionally, elevated HDL3-C levels were found to be an independent risk factor for CVC in HD patients (p =0.040). The ROC curve analysis showed an AUC value of 0.706 for HDL3-C (p =0.002).Conclusions: Our study indicates that elevated serum HDL3-C levels in HD patients are an independent risk factor for CVC and can serve as a potential predictor for CVC events. However, more studies need to verify its potential as a predictive indicator.